The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s1413-86702010000100016
|View full text |Cite
|
Sign up to set email alerts
|

Non Hodgkin's lymphoma with cutaneous involvement in AIDS patients: report of five cases and review of the literature

Abstract: Cutaneous B cell lymphoma (CBCL) is a lymphoproliferative disorder of neoplastic B cell of the skin with a wide range of clinical manifestations. Commonly, the clinical features of CBCL are plaques, nodules, or ulcerative lesions. Skin is one of the common sites for extra-nodal lymphomas in patients with AIDS and B cell type is less common than T cell type. Only recently, the existence of B cell lymphomas presenting clinically in the skin without evidence of extra-cutaneous involvement has been accepted as pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…Indeed, when we stratified AIDS-NHL in our study into systemic and CNS lymphomas, we observed that the increased AIDS-NHL risk was restricted to systemic lymphomas (OR 2.03, 95% CI 1.17-3.53) and not to CNS lymphomas (OR 0.77, 95% CI 0.29-2.04). However, B-cell AIDS-NHL located in the skin are rare [79][80][81] , and in our study only 3% (5/151) of TSPyV seropositive cases, and 2% (1/48) of TSPyV seronegative cases had skin-associated AIDS-NHL. Using the same multiplex serology assay for polyomaviruses, Teras and colleagues found no significant association between TSPyV seropositivity and NHL in immunocompetent people 82 .…”
Section: Discussioncontrasting
confidence: 56%
“…Indeed, when we stratified AIDS-NHL in our study into systemic and CNS lymphomas, we observed that the increased AIDS-NHL risk was restricted to systemic lymphomas (OR 2.03, 95% CI 1.17-3.53) and not to CNS lymphomas (OR 0.77, 95% CI 0.29-2.04). However, B-cell AIDS-NHL located in the skin are rare [79][80][81] , and in our study only 3% (5/151) of TSPyV seropositive cases, and 2% (1/48) of TSPyV seronegative cases had skin-associated AIDS-NHL. Using the same multiplex serology assay for polyomaviruses, Teras and colleagues found no significant association between TSPyV seropositivity and NHL in immunocompetent people 82 .…”
Section: Discussioncontrasting
confidence: 56%
“…In all, 276 published cases of PBL were identified from this search, which was then refined to identify those patients who presented with skin involvement. Twenty such patients were identified and are listed in Table together with their clinico‐pathological features.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated related risk of NHL associated with HIV infection is 100 times greater than in general population, and the risk increases with the progressive immunosuppression related with retrovirus. 4 More than 90%of HIV-associated NHL is derived from B cells and the majority is high grade. Extranodal presentation is most frequent in HIV-seropositive patients than in general population.…”
Section: Discussionmentioning
confidence: 99%
“…3 Patients with Non Hodgkins Lymphoma showed cutaneous involvement in 15% to 20% of cases and in 5% to 10% of them, skin lesions are the first manifestation of the disease. 4 Here we report a rare case of pyoderma gangrenosum (PG) with coexisting cutaneous non Hodgkins Lymphoma of diffuse large B cell lymphoma type in a HIV positive patient.…”
Section: Introductionmentioning
confidence: 98%